ANALISIS PERKEMBANGAN KEMAMPUAN KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH DI KOTA BITUNG (PERIODE 2008-2012) - Hetharia, Juliet Marla; Sabijono, Harijanto; Elim, Inggriani (Universitas Sam Ratulangi, 2014)
The paradigm of local financial management, both at the provincil and district/city experienced a significant change in line with the imlementation of regionel autonomy. In undergoing decentralization, local goverments are required to run the goverment that is effective, efficient, and able to support the community’s role in improving equity and justice by developing the full potential of each region by. Financial capacity of n area can be seen from the size of local revenue obtained the relevant area, in relation tothe granting of regional autonomy. The purpose of this study is to analyze the financial ability Bitung city areas in order to support the implementation of regional autonomy period 2008-2012. The data used is secondary data. The analytical method used is to calculate the area of financial ratios, among others, independence ratio, the ratio of the degree of fiscal decentralization, harmony ratio, the rti of routine capability index, dependency ratio, and the ratio of growth. The results showed (1) Independency Ratio still low, (2) The Ratio of the Degree of Fiscal Decentralization is still lacking, (3) Harmony Ratio is still low compared to regular shopping development spending, (4) Routine Capability Index Ratio is very less, (5) Dependency Ratio is very high and (6) Average Growth Ratio of positive and negative. From the research and data analysis can be conclude that the level of fiscal capacity Bitung city in support of regional autonomy for the period 2008-2012 are considered underprivileged.